Evaluation of the safety and efficacy of a donepezil depot injection in dogs with canine cognitive dysfunction - Kang, Min-Hee; Kang, Mi-Ae; Jeon, Hee-Jung; Shin, Ho-chul; Moon, Hana; Lee, Don-Gil; Park, Hee-Myung (Frontiers in Veterinary Science, 2025)
Canine cognitive dysfunction (CCD) is an age-related neurodegenerative disorder for which effective treatments remain limited, and objective diagnostic and therapeutic assessment tools using biomarkers or neuroimaging are still lacking compared with human Alzheimer’s disease. This study evaluated the safety and efficacy of a long-acting donepezil depot injection in dogs with CCD, using behavioral scores and serum neurofilament light chain (NfL) as primary outcomes, with baseline MRI for diagnostic support. Thirty-two dogs with clinically diagnosed CCD were randomly assigned to a high-dose group (n = 11), a low-dose group (n = 11), or a control group (n = 10). Diagnosis was established based on the Canine Cognitive Dysfunction Rating Scale (CCDR), the CAnine DEmentia Scale (CADES), and DISHAA scoring, and baseline MRI was performed in selected dogs with owner consent. A single intramuscular injection of donepezil depot was administered on day 0, and evaluations were conducted on days 14 and 28. The high-dose group showed significant improvements in CCDR, CADES, and DISHAA at both 14 and 28 days, whereas the low-dose group improved primarily at day 28, with earlier effects limited to CADES (p < 0.05). At day 28, both treatment groups had significantly lower serum NfL levels than controls (p < 0.05), while within-group values remained stable. Quality-of-life scores improved in activity, sociability, overall condition, and global QoL. Adverse events were mild and transient. These findings suggest that a single intramuscular injection of long-acting donepezil depot demonstrates favorable safety and potential efficacy in dogs with CCD, with improvements in behavioral scores and NfL supporting its therapeutic potential and highlighting the value of integrating clinical and biomarker-based assessments in future CCD management.